2014
DOI: 10.1371/journal.pone.0099131
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Quantitative Measurement of HER2mRNA Predicts Benefit from Trastuzumab-Containing Chemotherapy in a Cohort of Metastatic Breast Cancer Patients

Abstract: BackgroundWe sought to determine the predictive value of in situ mRNA measurement compared to traditional methods on a cohort of trastuzumab-treated metastatic breast cancer patients.MethodsA tissue microarray composed of 149, classified as HER2-positive, metastatic breast cancers treated with various trastuzumab-containing chemotherapy regimens was constructed. HER2 intracellular domain(ICD), HER2 extracellular domain(ECD) and HER2 mRNA were assessed using AQUA. For HER2 protein evaluation, CB11 was used to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…Furthermore, we characterized the mRNA expression of HER2 , CK19 , and CXCL10 (also known as IP-10 ) in combination with 16 antibodies in 70 samples from breast cancer patients. The HER2 gene is frequently genetically amplified in breast cancer patients, and HER2 mRNA expression levels have been shown to be highly correlated to genetic status and protein levels ( Vassilakopoulou et al., 2014 , Wang et al., 2013 ), making HER2 an ideal gene for validation of the system. CK19 is a type-1 cytokeratin often expressed in breast cancer that can be used as a marker to detect disseminated tumor cells in lymph nodes by mRNA or protein detection methods, but the mRNA-to-protein correlation in tissues is unknown ( Visser et al., 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we characterized the mRNA expression of HER2 , CK19 , and CXCL10 (also known as IP-10 ) in combination with 16 antibodies in 70 samples from breast cancer patients. The HER2 gene is frequently genetically amplified in breast cancer patients, and HER2 mRNA expression levels have been shown to be highly correlated to genetic status and protein levels ( Vassilakopoulou et al., 2014 , Wang et al., 2013 ), making HER2 an ideal gene for validation of the system. CK19 is a type-1 cytokeratin often expressed in breast cancer that can be used as a marker to detect disseminated tumor cells in lymph nodes by mRNA or protein detection methods, but the mRNA-to-protein correlation in tissues is unknown ( Visser et al., 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…There was a discrepancy at the protein level in the two studies, which used different scoring systems and found that the Hercept test scoring system may be not accurate enough to identify the correlation [ 40 , 41 ]. In metastatic setting, seven out of eight studies at DNA and mRNA level showed there was a positive correlation between HER2 amplification or mRNA expression level and response to trastuzumab or survival [ 43 – 49 ]. The only study that did not reach the limit of statistical significance was an explorative study with a small sample size of 33 [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on mRNA analysis, an additional 7% of breast cancer patients may be eligible for Herceptin therapy [ 51 ]. HER2 detection by RNAscope correlates well with immunohistochemistry and DNA-FISH [ 52 ]. HER2 expression could also be detected reliably by RNAscope in gastric cancer [ 53 ].…”
Section: Discussionmentioning
confidence: 99%